Reproductive and oncologic outcomes in young women with uterine sarcoma undergoing fertility-sparing treatment: a systematic review - Andrea Etrusco; Vittorio Agrifoglio; Antonio Simone Laganà; Elko Gliozheni; Annamaria Caringella; Antonio Stanziano; Ettore Cicinelli; Vito Chiantera; Andrea Giannini; Baydaa Alsannan; Fabio Barra; Antonio D'Amato (SAGE Publishing, 2024)
Background: Uterine sarcomas (US) are rare cancer of possible occurrence even in women of childbearing age. To date, total hysterectomy is the standard treatment in the early stages. The possibilities of carrying out fertility-sparing treatments (FST) to save the fertility of women with unfulfilled reproductive desires are described in the literature, but to date, they can only be considered experimental. Objective: The aim of this systematic review was to evaluate the oncological and reproductive outcomes of women with different histological types of US undergoing FST. Design: Systematic review. Data sources and methods: Electronic databases were searched for English-language studies describing FST for US until January 31, 2024. Results: Forty-five papers which met the abovementioned inclusion criteria, were included in the qualitative analysis. Quantitative analysis was not possible because of the heterogeneity of the data. A descriptive summary of the results according to the histotype of US was provided. Six hundred forty-one patients of childbearing age with US and undergoing FST. After treatment with FST, 89 (13.9%) disease recurrences and 107 (16.7%) pregnancies were recorded. Conclusion: In selected cases of early-stage US, FST may be proposed. However, the patient must be informed of the real possibility of recurrence and potentially difficult achievement of pregnancy. Additional well-designed prospective studies and clinical trials are needed to address the knowledge gaps and enhance clinical decision-making in this population. Trial registration: PROSPERO ID: CRD42024509356.